On Measuring the Effects of Fiscal Policy in Recessions - Parker, Jonathan A (Journal of Economic Literature, 2011)
We do not have a good measure of the effects of fiscal policy in a recession because the methods that we use to estimate the effects of fiscal policy—both those using the observed outcomes following different policies in aggregate data and those studying counterfactuals in fitted model economies—almost entirely ignore the state of the economy and estimate “the” government multiplier, which is presumably a weighted average of the one we care about—the multiplier in a recession—and one we care less about—the multiplier in an expansion. Notable exceptions to this general claim suggest this difference is potentially large. Our lack of knowledge stems significantly from the focus on linear dynamics: vector autoregressions and linearized (or close-to-linear) dynamic stochastic general equilibrium (DSGE) models. Our lack of knowledge also reflects a lack of data: deep recessions are few and nonlinearities hard to measure. The lack of statistical power in the estimation of nonlinear models using aggregate data can be addressed by exploiting estimates of partial-equilibrium responses in disaggregated data. Microeconomic estimates of the partial-equilibrium causal effects of a policy can discipline the causal channels inherent in any DSGE model of the general equilibrium effects of policy. Microeconomic studies can also provide measures of the dependence of the effects of a policy on the states of different agents, which is a key component of the dependence of the general-equilibrium effects of fiscal policy on the state of the economy. (JEL E12, E13, E32, E62, H50)